Ultrasound-Guided Interventions of the Foot and Ankle - Yablon, Corrie M. (Seminars in Musculoskeletal Radiology, 2013)
Ultrasound (US) provides excellent delineation of tendons and ligaments in the foot and ankle and provides real-time visualization of a needle during interventions, yielding greater accuracy and efficacy than the traditional blind approach using anatomical landmarks. For this reason, US is rapidly gaining acceptance as the preferred modality for guiding interventions in the foot and ankle where the anatomy is complex, neurovascular structures should be identified, and precise technique is demanded. In the foot and ankle, US is especially useful to guide tendon sheath, bursal, and Achilles paratenon injections, Morton neuroma injections, plantar fascial injections, and joint aspirations and injections.
Keywords: foot; ankle; injection; ultrasound guidance